STRENGTHENING MSMES BASED ON SHARIA ECONOMIC LAW FOR FAIR AND SUSTAINABLE BUSINESS - Fitri Nasution; Muhammad Yusup; Zilawati; Agus Tri Santoso; Rina Rodiana; Farmila; Thiara Meilany; Novita Hardiani; Risma Yuliandari (International Journal of Multidisciplinary Reseach, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the national economy, particularly in creating employment and reducing poverty. However, many MSMEs still face challenges in legal protection, access to financing, and sustainable business practices. This community service program aims to strengthen MSMEs through the application of Sharia Economic Law principles to create fair, ethical, and sustainable businesses. The program was implemented through socialization, mentoring, and training on sharia-based contracts, halal business management, and Islamic financial literacy. The results show an increased understanding among MSME actors regarding sharia contracts (akad), halal business practices, and ethical trade principles such as justice, transparency, and mutual benefit. This program contributes to building legally aware MSMEs that are not only economically productive but also socially responsible and sustainable.